2020
DOI: 10.3389/fmed.2020.589079
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Autonomic Nervous System and Rheumatoid Arthritis: From Bench to Bedside

Abstract: Neuronal stimulation is an emerging field of research focused on the management and treatment of various diseases through the reestablishment of physiological homeostasis. Electrical vagus nerve stimulation has recently been proposed as a revolutionary therapeutic option for rheumatoid arthritis (RA) in combination with or even as a replacement for conventional and biological drugs. In the past few years, disruption of the autonomic system has been linked to RA onset and activity. Novel research on the link be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 154 publications
0
23
0
Order By: Relevance
“…As in other autoimmune diseases, it has been demonstrated that ANS plays a role in RA. Indeed, ANS dysfunction affects target organs (i.e., heart, kidney, and blood vessels), and it is also strongly interrelated with the onset and perpetuation of chronic inflammation via the ‘inflammatory reflex’ [ 111 ]. Signs of autonomic impairment in RA have been observed since the late 1950s [ 112 ]; however, the cause–effect and the temporal relationship between the onset of ANS dysfunction and inflammation is still a matter of current research.…”
Section: Autonomic Nervous System and Its Interplay With Inflammation...mentioning
confidence: 99%
See 2 more Smart Citations
“…As in other autoimmune diseases, it has been demonstrated that ANS plays a role in RA. Indeed, ANS dysfunction affects target organs (i.e., heart, kidney, and blood vessels), and it is also strongly interrelated with the onset and perpetuation of chronic inflammation via the ‘inflammatory reflex’ [ 111 ]. Signs of autonomic impairment in RA have been observed since the late 1950s [ 112 ]; however, the cause–effect and the temporal relationship between the onset of ANS dysfunction and inflammation is still a matter of current research.…”
Section: Autonomic Nervous System and Its Interplay With Inflammation...mentioning
confidence: 99%
“…Parasympathetic nervous system (PNS) hypoactivation and sympathetic nervous system (SNS) hyperactivity may exert their pathogenetic effect directly impacting the CV system and through an impairment of the cholinergic anti-inflammatory pathway. In RA, an imbalance in PNS-SNS stimulation may lead to a defective release and binding of acetylcholine to the α7nAChR on splenic macrophages and fibroblast-like synoviocytes in the joints with a consequent uncontrolled release of proinflammatory cytokines (e.g., TNF, IL-1, and IL-6) and self-sustaining chronic inflammation of target organs (e.g., joint and bone damage and accelerated atherosclerosis) [ 2 , 111 ].…”
Section: Autonomic Nervous System and Its Interplay With Inflammation...mentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have shown that vagus nerve stimulation can effectively reduce disease severity and inflammatory responses in diseases such as rheumatoid arthritis, colitis, acute kidney injury, and pancreatitis. 19 , 20 FMIE preserves the pulmonary branch of the vagus nerve, which may reduce pulmonary inflammation. These features may explain the lower inflammatory response in patients who underwent FMIE.…”
Section: Discussionmentioning
confidence: 99%
“…Another important class of therapeutics is disease-modifying antirheumatic drugs (DMARDs), such as methotrexate, leflunomide, sulfasalazine, and hydroxychloroquine [ 9 , 10 ]. They act to alleviate pain and inflammation, minimize or prevent joint deterioration, and preserve joint structure and function via suppressing the body’s overactive immune and/or inflammatory systems [ 11 ]. Leflunomide (Lfd), N [(4-trifluoromethyl) phenyl]-5-methylisoxazole-4-carboxamide, is a synthetic isoxazole derivative that possesses anti-inflammatory as well as immunosuppressive properties, and has been licensed as an anti-arthritic drug by The United States Food and Drug Administration (USFDA) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%